Experimental and theoretical study for the determination of thermal conductivity of porous building material made with pumice and tragacanth - Kocyigit, Fatih; Akpinar, Ebru Kavak; Bicer, Yasar (Taylor & Francis Ltd, 2016)
In this study, porous solid materials were produced with mixture combinations of materials such as tragacanth, cement, and pumice aggregate. Thermal conductivities of the produced materials were determined using hot wire methodology. The thermal conductivities of the produced samples ranged from 0.433 to 0.177 W/mK, depending on pumice diameter, pumice, tragacanth, and cement rates. A new model was developed to determine the effective thermal conductivities of the produced samples. The thermal conductivities obtained by the measurements were compared to the ones predicted by the model. The predicted values deviated as 1-31% from the measured values. It was finally shown that the experimental results were in good agreement to the predicted results.
Keywords: Porous solid material; pumice; tragacanth; thermal conductivity